RESULTS OF TOXICITY STUDY OF BIOLOGICAL FERTILIZER "YER MALHAMI" FOR INHALATION CHRONIC EFFECTS - Guzal F. Sherkuzieva; Feruza I. Salomova; Nargiz R. Samigova; Feruza U. Yuldasheva (Central Asian Journal of Medicine, 2023)
Population growth is forcing followers to seek ways to increase food production. One such way is to increase the productivity of crops by providing them with additional sources of nitrogen bound. In recent years, Uzbekistan has made extensive use of bio-preparations in agricultural production, and new branches of the biological industry - bio-factories and bio-laboratories - have been established. Consequently, the number of workers in contact with biological pollutants that are not safe for human health is increasing. Methods of research: The subject of our research was biological fertilizer "Yer malhami". The study of the toxicity and nature of biofertilizer biological activity was carried out in accordance with the requirements of the guidelines "Towards the formulation of studies to substantiate the MAC of bioinsecticides of the environment", and "Guidelines for the Integrated Hygienic Assessment of New Pesticides", Guidelines for the Definition of Plant Biological Protection Agent "Yer Malhami" in the Ambient Air and Air Working Area. A chronic four-month inhalation experiment. Conclusion: Generalizing the results of the 4-month biofertilizer exposure of white rats, 483.3 mg/m3 toxic, 48.6 mg/m3 threshold and 9.76 mg/m3 - inactive.